Applying qualitative research in management studies - theory and practical experiences: Using NVivo 15 - Van, Thanh Ta; The, Hien Dang; Van, Trung Vu; Van, My Dang (International Journal of Innovative Research and Scientific Studies, 2025)
In response to the difficulties that students and researchers often encounter when applying qualitative research methods in dissertations, theses, and scientific papers, this article offers a conceptual overview of qualitative research, emphasizing the primary methods relevant to management studies. Particular attention is given to the grounded theory approach, which enables researchers to develop theoretical models based on empirical data. The study presents a step-by-step guide for conducting qualitative research using grounded theory as a methodological framework. By providing a structured explanation of the grounded theory process, the article clarifies how researchers can systematically collect, code, and analyze qualitative data to construct or refine theoretical frameworks within the context of management research. Grounded theory is highlighted as a valuable methodological approach for exploring complex phenomena in depth and generating theory grounded in real-world observations. This article enhances understanding of the effective implementation of this approach. Furthermore, the study offers practical guidance for graduate students and early-career researchers in the field of management who wish to adopt qualitative methods, particularly grounded theory, in their academic work. The clearly defined methodological roadmap presented in this article serves as a useful reference for improving the rigor and credibility of qualitative research.